TEACHERS’ PERCEPTION OF THE USE OF GEOGEBRA APPLET IN A NATIONAL UNIVERSITY IN PERU - Cenas Chacón, Fernando Ysmael; Vargas Vera, Luis Fernando; Monroy, Jorge Luis; Ramírez Sobalvarro, Yasmina (LACCEI, 2025)
The purpose of this study was based on the need to describe the perception that teachers have about the use of Applet for teaching GeoGebra at a national university in Trujillo in the Faculty of Physical and Mathematical Sciences, in the year 2024, a situation that was revealed from the experience shared by forty teachers through a Google Forms questionnaire. from their opinions, it was possible to know the practice developed where 38% of the participating teachers stated that they have had university experience for more than eleven years, on the other hand, 33% are very familiar with the use of this tool and 67% of them recognize that the main challenge for the development of this resource is the time required for the proper planning and construction of the same, prior to its use in class sessions. For 52% of the teachers, the use of technology in the development of their courses indicated that it improves participation and motivates university students to experiment with new ways of applying theoretical content. It is an important challenge for teachers to carry out the preparation of the applets, adjusting them to the fulfillment of the objectives of the class sessions, and it is recognized that it is essential to provide ongoing training on the benefits of technology as a tactic that favors the development of skills for both teachers and students.